Effects of a work-stress intervention in Swedish primary care versus treatment as usual: RCT-study. (13th November 2019) - Sandheimer, C; Hedenrud, T; Hensing, G; Holmgren, K
Abstract: Background: Work stress is an increasing burden in society. To identify early symptoms of work stress in primary health care (PHC) could result in earlier and better adjusted care. A work stress questionnaire (WSQ) was developed in PHC for this task. We aimed to evaluate if the use of WSQ, in combination with physician's feedback, results in differences in health care visits and treatment compared to treatment as usual (TAU) in patients reporting high stress. Our hypothesis was that patients receiving the intervention would generate more visits to rehabilitation providers during follow-up compared to TAU. Methods: A two-armed RCT was conducted at seven primary health care centres (PHCC) in Region Västra Götaland, Sweden. One group received the WSQ-intervention and the controls received TAU. Employed not sick-listed persons aged 18-64 that sought care for mental and physical health complaints at the PHCCs participated. Register data on health care visits and treatments 12 months prior inclusion and 12 months after was obtained and analysed with Fisher's exact test together with questionnaire data (WSQ and background features). Results: A total of 271 participants were included in the study, 132 intervention and 139 controls. The proportion that visited psychologists/psychotherapists was higher among the intervention group with high stress (19.5%, n = 87) during follow-up compared to corresponding controls (7.2%, n = 97) (p = 0.048). Collaborative care measures were more common among the stressed intervention participants (23%) post-inclusion compared to the stressed controls (11.3%) (p = 0.048). Conclusions: Significant differences were found between the WSQ intervention group and the controls reporting high stress in visits to psychologists and in amount of received collaborative care. This confirms our hypothesis that the WSQ can help physicians to identify work stress and give suitable rehabilitative measures at an earlier stage in the care process compared to TAU. Key messages: The use of WSQ with physicians' feedback generated more visits to psychologists and more received collaborative care compared to treatment as usual. Findings of the study indicate that the WSQ can assist in identifying work stress in primary care and accommodate rehabilitative measures compared to treatment as usual.